An Analysis of The Implementation of Merdeka Curriculum in English Teaching Learning SMPN 14 Bengkulu - Fabela, Putri; Zasrianita, Fera; Febriani, Hanura (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This study aims to analyze the implementation of the merdeka curriculum in English teaching learning at SMPN 14 Bengkulu City and what were challenges and opportunities that they were faced by them in the learning process. This research was based the greater flexibility for teachers and students in the teaching learning process with a focus on developing students competencies, characters and also many teachers were still inconsistent for implementing the merdeka curriculum in the learning process because of there were certain factors that made it difficult for teachers to implement it such as, the lack of teacher readiness in implementing the merdeka curriculum, limited training or understanding of teachers, lack of resources and facilities, old habits that are difficult to abandon, and lack of student readiness.  This study used qualitative descriptive research. Research data were obtained through observation, in-depth interviews and documentation. This study also used reduction data analysis techniques, data display, and conclusion or verifying data. Researchers also used trustworthiness of the data to get a reliable data to collect valid data. The results of the study showed that the implementation of the merdeka curriculum in English learning has a positive impact on student motivation and participation. Teachers has more freedom in designing and adapting learning materials according to their needs and asking students. However, this study also found several challenges and opportunities, such as limited resources and technical support, as well as the need for further training for teachers to understand and apply the principle of merdeka curriculum effectively. Meanwhile, the opportunity obtained is that teachers are required to be proficient in using digital and can utilize technology in learning.